Comparative Stress Evaluation between Bilayer, Monolithic and Cutback All-Ceramic Crown Designs: 3D Finite Element Study - Ramos, Nathalia de Carvalho [UNESP] (2021)
Different all-ceramic crown designs are available to perform indirect restoration; however, the mechanical response of each model should still be elucidated. The study aims to evaluate the stress distribution in three different zirconia crown designs using finite element analysis. Different three-dimensional molar crowns were simulated: conventional bilayer zirconia covered with porcelain, a monolithic full-contour zirconia crown, and the cutback modified zirconia crown with porcelain veneered buccal face. The models were imported to the computer-aided engineering (CAE) software. Tetrahedral elements were used to form the mesh and the mechanical properties were assumed as isotropic, linear and homogeneous materials. The contacts were considered ideal. For the static structural mechanical analysis, 100 N occlusal load was applied and the bone tissue was fixed. Maximum principal stress showed that the stress pattern was different for the three crown designs, and the traditional bilayer model showed higher stress magnitude comparing to the other models. However, grayscale stress maps showed homogeneous stress distribution for all models. The all-ceramic crown designs affect the stress distribution, and the cutback porcelain-veneered zirconia crown can be a viable alternative to adequate function and esthetic when the monolithic zirconia crown cannot be indicated.